The Situational Leadership Styles of Primary Grades Teachers in Early Childhood Schools according to Hersey and Blanchard's Theory during the Changes in the Educational Systems - Khomais, Sama Fouad; Al Sultan, Rana Hezam (Journal of Educational and Psychological Sciences, 2024)
The study aimed to explore the situational leadership styles of primary grades teachers in early childhood schools according to Hersey and Blanchard's theory during the changes in the educational systems and to uncover differences in the situational leadership styles’ practices among the sample, which are attributed to some demographic variables (educational qualification, specialization, years of experience). The study used a descriptive-analytical approach, and the sample consisted of 306 primary-grade teachers working in public early childhood schools in Makkah City. The study tool was the "Hersey and Blanchard" measure. The study found that the predominant leadership style among primary grades teachers was the persuasive style, obtaining the highest percentage at 51.0%, followed by the participative style at 30.7%, then the telling or directive style at 15.7%, while the delegating style was the least used, with a percentage of 2.6%. This can be explained by the students’ need for continuous follow-up and constant guidance, as well as communication and psychological support in this stage. The study also showed that there were no statistically significant differences in situational leadership styles among early childhood teachers attributed to educational qualification, specialization, and years of experience. The study recommends promoting leadership practices among teachers by providing classroom environments with appropriate specifications as well as providing professional development opportunities while working to add educational leadership courses in teacher preparation programs in universities and institutes.
Keywords: Situational leadership; early childhood teachers; primary grades; educational systems; Hersey and Blanchard's theory